IMPLEMENTASI MANAJEMEN PEMBIAYAAN PENDIDIKAN TPQ ROUDLOTUT THOLAB - Agus Miftakus Surur; Maulana Sanjaya (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
This study aims to find out about how the implementation of financing management in non-formal educational institutions, namely TPQ. The study conducted research at a TPQ named TPQ Roudlotut Tholab. The research method used is a qualitative research method using a PAR (Participatory action research) approach. The researcher used the approach because the researcher went directly to the research location, namely TPQ Roudlotut Tholab. In this research, the researcher uses secondary data and primary data provided by one of the administrators at TPQ Roudlotut Tholab. The results in this study are the source of funds for TPQ Roudlotut Tholab comes from infaq of the guardians of students at TPQ Roudlotut Tholab and also assistance from the government. Budget management at TPQ Roudlotut Tholab is also very good, this can be seen from the meetings that are often held by the students of TPQ Roudlotut Tholab before entering the new school year. In terms of the use of the financing budget at the Roudlotut Tholab TPQ, it doesn't cost too much, but during this COVID-19 pandemic, the spending budget at the Roudlotut Tholab TPQ is very large, especially if you have to comply with health protocols. TPQ Roudlotut Tholab in carrying out the health protocol to buy buckets and hand washing soap, this was done because he wanted to break the chain of the spread of Covid-19, which spread so quickly in our country, Indonesia. Keyword: Management, Financing, Education, TPQ